Tanggung Jawab Mahasiswa terhadap Kebersihan Lingkungan di Fakultas Ilmu Sosial Universitas Negeri Medan - Sri Yunita; Pingky Monica Hasugian; Tessa Lonika Simanullang; Limra Nababan (Journal on Education, 2023)
The purpose of this research is to find out how students are responsible for environmental cleanliness on campus, especially at the Faculty of Social Sciences, Medan State University. inductive. The source of the data in this study were students of the Faculty of Social Sciences, Medan State University. The results showed that there were still many students who were not aware of their responsibility to be responsible for environmental cleanliness. Obligation to be responsible for Environmental Cleanliness as a Student.